Effectiveness of management in public administration in complex and crises situations - L. Korolchuk, Olena (2020)
The solvency crisis of 2020, exacerbated by the Covid-19 pandemic, necessitates a study of the effectiveness and relationship of crisis management in public administration. This study is based on the concepts of neo-institutionalism, attribution and organized legitimacy. The article confirms the importance of using the principles of these theories based on statistical analysis using the Granger test and a regression model based on panel data from transition economies. First of all we will review The Worldwide Governance Indicators (WGI) of transition economies for 1996-2018 and explore the relationship between public governance indicators and the effectiveness of crisis management.